Stomach contents of the Pacific sharpnose shark, Rhizoprionodon longurio (Carcharhiniformes, Carcharhinidae) in the southeastern Gulf of California - Yolene R Osuna-Peralta; Domenico Voltolina; Ramón E. Morán-Angulo; J. Fernando Márquez-Farías (Latin American Journal of Aquatic Research, 2014)
The feeding habits of the sharpnose shark Rhizoprionodon longurio of the SE Gulf of California are described using the stomach contents of 250 specimens (135 males and 115 females) obtained weekly from December 2007 to March 2008 in the two main landing sites of the artisanal fishing fleet of Mazatlan. The mean total length (TL) was 77.7 ± 12.8 cm and the respective ranges for males and females were 60-120 cm and 52120 cm. Size distribution showed two modal groups (juveniles: 52-80 cm, mode 72.5 cm, and adults: 85-140 cm, mode 92.5 cm). Out of the 395 preys identified in 235 stomachs with identifiable contents, the most important were cephalopods (Index of Relative Importance, IRI = 93.1%), mainly Argonauta spp. (IRI = 92.9%). The total IRI value for fish was 5.9%, mostly represented by Oligoplites refulgens and Oligoplites sp. (joint IRI value = 4.8%). The diversity of the stomach contents of males and females was not significantly different, and although the values of diversity, equitability and dietary breadth indexes were lower in juveniles than in adults, ANOSIM analysis did not show differences in dietary habits related to age and sex. The results indicate a specialized feeding behaviour, with Argonauta spp. as preferred prey. This behaviour does not agree with all previous information on R. longurio, and is probably due to local availability of this prey during the sampling period.